1999
DOI: 10.1046/j.1460-9568.1999.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Limbic P300s in temporal lobe epilepsy with and without Ammon's horn sclerosis

Abstract: Limbic P300 potentials can be recorded within the mesial temporal lobes of patients with temporal lobe epilepsy (TLE). To delineate possible mechanisms of their generation and pathological alteration, we analysed limbic P300s in 55 TLE patients with and 29 without Ammon's horn sclerosis (AHS) and correlated their amplitudes with neuronal cell counts in 30 histopathological specimens. Limbic P300 amplitudes were reduced on the side of the epileptogenic focus only in patients with AHS. Moreover, in AHS patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
41
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 46 publications
5
41
0
Order By: Relevance
“…Since explicit memory and the P600 are linked to the hippocampus (Düzel et al 2001;Fernández et al 1999; Grunwald et al 1999), these results are consistent with previous investigations indicating that glucocorticoids affect hippocampal function. The pattern of the P600 component was particularly interesting.…”
Section: Discussionsupporting
confidence: 90%
“…Since explicit memory and the P600 are linked to the hippocampus (Düzel et al 2001;Fernández et al 1999; Grunwald et al 1999), these results are consistent with previous investigations indicating that glucocorticoids affect hippocampal function. The pattern of the P600 component was particularly interesting.…”
Section: Discussionsupporting
confidence: 90%
“…Both in the rhinal cortex and hippocampus, the amplitudes of ERP components elicited by deviants exceeded those of standard tones. The amplitudes of these ERP components were relatively small and amounted to about 90 % less, as compared to active oddball paradigms (Halgren et al, 1995;Grunwald et al, 1999). For the hippocampal activity elicited by deviants, a response decrease was observed within the course of the experiment.…”
Section: Discussionmentioning
confidence: 81%
“…Drake et al [1986] showed a longer latency of P3 in partial nonlesional epilepsy. Hippocampal sclerosis (HS) appears to have a specific impact too, since Grunwald showed a bilateral P300 latency increase in this population [Grunwald et al, 1999]. Given that 6 of our 10 patients suffer from HS, the impact of this specific aetiology should not be underestimated.…”
Section: Discussionmentioning
confidence: 88%